THE ANALYSIS OF A COMPANY’S FINANCIAL PERFORMANCE BEFORE AND AFTER IMPLEMENTING THE INITIAL PUBLIC OFFERING (A STUDY ON THE COMPANY LISTING IN THE IDX OF 2018) - Syaiful Arif; Bambang Santoso Marsoem (Dinasti Publisher, 2021)
This study aims to discover the differences in financial performance before and after the IPO for companies that went public in 2018. The sampling method was the purposive sampling with 17 companies in total as samples. The financial performance is assessed from the ratio of liquidity, activity, solvability, and profitability. Differences in performance were tested with the paired sample t-test and the Wilcoxon signed rank test. Implementing the basis of the liquidity and solvability ratios, there were improvement differences in companies’ financial performances after the IPO. Meanwhile, by implementing the basis of the activity and profitability ratios, there were declining differences in the companies’ financial performances after the IPO. Throughout thee period of two years and one year after the IPO, there have been both post-IPO changes and stagnations in the hypothesis of the profitability ratio, which concluded that the companies’ ability to seek profit would require a certain period of time.